Underactive Bladder; Diagnosis and Treatment at BSMMU; Single Centre Retrospective Study - Ullah, ATM Aman; Hossain, Muhammad; Rahman, Md Habibur; Alam, AKM Khurshidul (Bangladesh Journal of Urology, 2020)
There have been no universally agreed upon criteria and categorization of the underactive bladder (UAB). This study describes the clinical and urodynamic characteristics of UAB with lower urinary tract symptoms and treatments, and attempts to provide a system of categorization. Objective: Some patients with Lower urinary tract symptoms (LUTS) have underactive bladder and their treatment options vary subjectively. This study attempts to investigate the patient-reported experience of treatment after UDS. Materials and methods; A retrospective study was conducted at the urology department at BSMMU from April 2017 to Dec 2019. Contraindication was Urinary Tract Infection (UTI). Patients were monitored according to follow up schedule. Results: Total number of UAB was 151. Initial complication was minimum; only two patients had UTI. Most patients improved with conservative management and CIC. The rest retain their symptoms with other treatments. Conclusion: Conservative method and CIC is the main treatment for UAB. There are still many unknown causes for UAB, and many treatments are still unavailable in our country, it is still controversial whether satisfactory success is achieved in the treatment of patients with UAB. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.24-30